Existing Within Confines: Ecology, Sustainability, and the Future Ecological Outlook in Amitav Ghosh’s The Hungry Tide - Shalini Jayakumar A. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Amitav Ghosh’s The Hungry Tide portrays the Sundarbans not merely as a setting, but as a dynamic ecological force, challenging the concept of “Human Exceptionalism.” The narrative critiques “fortress conservation,” illustrating through the Morichjhapi massacre how environmental protection often disenfranchises marginalized communities. By contrasting scientific ecology with indigenous wisdom, the text argues that sustainability depends on reconciling these perspectives. It proposes a shift toward a “flat ontology,” viewing humans and nature as equal participants in a shared web of life. Ultimately, the novel asserts that ecological survival is inseparable from social justice and historical memory.